The cinema of Richard Linklater : walk, don't run - Stone, Rob (Directors' cuts., 2013)
From Slacker (1991) to The School of Rock (2003), from Before Sunrise (1995) to Before Sunset (2004), from the walking and talking of his no/low-budget American independent films to conversing with the philosophical traditions of the European art house, Richard Linklater's films are some of the most critical, political, and spiritual achievements of contemporary world cinema. Examinations of Linklater's collaborative working practices and deployment of rotoscoping and innovative distribution strategies all feature in this book, which aspires to walk and talk with the filmmaker and his fil.